Analysis of Android-Based Learning Media Needs in Social Sciences (IPS) Learning - Astri, Astri (Universitas Sang Bumi Ruwa Jurai, 2024)
This study aims to determine the needs of students for android-based learning media in social studies. This research method is quantitative with research subjects homeroom and class IVB students at SDN Pabuaran 1 Tangerang. The instruments used in this study were a questionnaire and a structured interview. Based on the results of interviews with teachers, it shows that teachers have never designed android-based learning media. Meanwhile, based on the results of student needs, it shows that 100% of students use Android smartphones, 61.9% use them every day (morning, afternoon, and evening), but it is unfortunate that 45% use it to watch YouTube and only 10% of students use it to study. Meanwhile, based on the subjects of interest, it was shown that 47.6% Indonesian, 19% Natural Studies, 19% Mathematics, and 0% Social Studies. In addition, 95.2% of students agree with the development of android applications. Based on the results of these studies, it can be concluded that it is necessary to consider android-based learning media in social studies in elementary schools.